Preparing the next generation of teacher educators for clinical practice - Yendol-Hoppey, Diane; Dana, Nancy Fichtman, 1964-; Hoppey, David (Advances in teacher education., 2019)
"Today, in many contexts the lack of attention to preparing the next generation of teacher educators as well as having a critical mass of faculty who understand the current teacher education research problem lingers. Although the NCATE Blue Ribbon Panel Report (2010), the recent advent of the CAEP standards, and the new AACTE Clinical Practice Commission Report (2017) challenge those responsible for teacher preparation to rethink the design as well as their work within clinical practice, many teacher education faculty do not work beyond "their duty of teaching a course" (Ziechner, 1999, p. 11) and there is much too little discussion about how to prepare the next generation of teacher educators to work differently. Teacher education too often remains "a tangential concern for most and the major concern of only a few" (p.11). These concerns raise important questions for those who are currently responsible for pivoting, reinventing, and researching teacher preparation. Indeed, the literature lacks important attention to the preparation of teacher educators. This book offers insights from teacher education researchers that illustrate the ongoing benefits and persistent challenges of educating and preparing university and school-based teacher educators. This is an important step in understanding the complex roles, practices, and responsibilities associated with high quality teacher education that emphasizes clinical practice"--